Sistem Informasi Kemitraan Berbasis Website dengan Integrasi E- Proposal dan Payment Gateaway Di PT. LEN Industri - Mohammad Iqbal Mohammad Iqbal (JSAI (Journal Scientific and Applied Informatics), 2022)
PT. Len Industri has an empowered partnership program to provide capital loans and business training for MSMEs in increasing productivity and business quality. The implementation of this partnership program has a positive influence on MSMEs, namely by expanding the scope of the business area to touch the international market. However, behind these successes and achievements, there are several problems in the partnership program at PT. The current Len Industries include: MSMEs must apply for partner programs by visiting the main office directly to find out information, submitting applications to become partners and borrowing funds, this is certainly less time efficient. In addition, the recording of transactions that are currently running on the partnership program is still manual, namely by uploading proof of transactions which if partners forget to report it will be a problem and the data is less organized. One of the solutions proposed to deal with the above problems is to build a system in digital form that is easily accessible and can only be accessed by interested parties. So a partnership information system was designed in the form of a website with the SDLC system design method with a focus on development using the prototype method. Optimization of proposal submission activities as partners and submission of funds is carried out using the electronic proposal method (e-proposal) which has been provided by the system automatically without having to go to the main office. In addition, this website-based partnership information system has been integrated with a payment gateway service, enabling interested parties to conduct transactions in a system with more organized data settings. The Partnership Information System created by Ayuba Dharma Putri as a student of this information systems study program has been tested by testing using black box testing with a 100% success percentage, without failure. Assessment of user satisfaction is carried out through User Acceptance Testing (UAT) which produces a percentage of 86% and is categorized as very feasible to use.